Barrier mechanisms in the developing brain: protection or vulnerability? - Saunders, Norman (Henry Stewart Talks, 2014)
The brain develops within a well-defined internal environment, The properties of this internal environment are determined by transporters in the cellular interfaces between the blood, brain and cerebrospinal fluid, The transporters are effective because the intercellular spaces between the cells in the interfaces are sealed by tight junctions, The transporters are both influx and efflux and many are active very early in brain development, Although brain barrier mechanisms are present very early in development they are vulnerable to pathological conditions e.g. inflammation, which may result in barrier dysfunction and damage to the fragile developing brain, These mechanisms thus provide protection and a stable internal environment, but some may render the developing brain more vulnerable e. g. inward transport of toxins such as mercury via a normal amino acid transporter
Archived at 2018/05/31